Analisis Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Usaha Pada Koperasi Kredit Citra Hidup Tribuana Kalabahi Kabupaten Alor - Marteda Olang (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect analysis of cash turnover and accounts receivable turnover on business profitability at the Citra Living Credit Coomperative, Tribuana Kalabahi , Alor Regency. This type of research is quantitative research with data collection techniques, namely observation, interviewis , and documentation. This study uses population secondary data and the sample is the financial resports of the Citra Living Credit Coomperative, Tribuana Kalabahi, Alor Regency in the 2018-2022 period. The statistical method used in this study is multiple linear regression by looking at the significant value of the t test and the significal value of the F test as a benchmark in returning the hypothesis and the results of data processing using the help of the IBM SPSS 25 for windows. The results of this study indicate that: 1) Partially the cash turnover variable has a significant value of 0,000 or 0,0% where this value is smaller thant the alpha value of 0,05 or 5% that the results of this research are Enetima H1 which states thant the cash turnover variable partially has a positive effect on business profitability in the Citra Living Credit Coomperative, Tribuana Kalabahi, Alor Regency. 2) Partially the receivables turnover variabel has a significant value of 0,000 or 0, 0% where this volue is smaller that the alpha value of 0,05 or 5% so that the results of this study accept H2 which states that the receivables turnover variable partially has a positive effect on profitability business at the image of life Credit Coomperative Tribuana Kalabahi Alor Regency. 3)Simultaneously the variables of cash turnover and account receivable turnover have a significant value of 0,000 or 0,0% where this volue is smaller than the alpha value 0,05 or 5% so that the results of this study simultaneously accept H3 which states that the variable cash turnover and receivable turnover simultaneously has a positive effect on business profitability in the Citra Living Credit Coomperative, Tribuana Kalabahi, Alor Regency.